Description of the Emotional Mental Health of Elementary School Children Who use Smartphones at Public Elementary School 064979 Medan - Rotua Elvina Pakpahan; Friska Sembiring; Winda Triwayuli Sinaga (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Introduction: Elementary school children play a very important role in the development stages of children in their middle and final stages of childhood. Children's emotional mental health can also influence their own future, and have a big impact on family, friends, teachers and society, because Parents need to supervise their children when using smartphones. The duration of smartphone use for children aged 3-S years is 1 hour per day and for children aged 6-18 years is 2 hours per day. Method:The design of this research is a quantitative descriptive design using a cross sectional approach. The samples for this research are 71 students using a total sampling technique. The measuring tool for this research used the SDQ (Strength & Difficulties Questionnaire) questionnaire. There are 5 categories or aspects of behavior that are measured to detect emotional mental health, namely emotional problems, behavioral problems, hyperactivity, peer problems, and prosocial, each category has 3 divisions, Normal Borderline, Abnormal. Result:The research results obtain are Normal 4 (5.6%), Borderline 62 (87.4%). Abnormal are 5 (7.0%). Conclusion:It is hoped that this research will provide input for elementary school children so that they can adapt to their environment. Parents also play a very important role for children so that children do not become addicted to smartphones.